2009
DOI: 10.1007/s00268-008-9860-x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Breast Cancer in a Group of Women in a Developing Country in South Asia: Is There a Difference?

Abstract: The overall profile of breast cancer and immune characteristics of Sri Lankan women in this study was largely comparable to profiles documented elsewhere in the region despite the lower prevalence of ER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 14 publications
2
32
2
Order By: Relevance
“…Lokuhetty et al reported a mean age at presentation of 52 years with 32% of patients between 50 to 59 years of age [9]. …”
Section: Resultsmentioning
confidence: 99%
“…Lokuhetty et al reported a mean age at presentation of 52 years with 32% of patients between 50 to 59 years of age [9]. …”
Section: Resultsmentioning
confidence: 99%
“…Additional studies from India and Sri Lanka also report a high prevalence of ER-negative breast cancers [ Table 4]. [28][29][30] A common feature of these countries is that they are all poor countries with generally poor sanitation, lack of clean drinking water, relative inaccessibility to health care and medicines (especially antibiotics), and crowded living conditions. All of these factors contribute to frequent exposures to infectious agents, beginning at an early age.…”
Section: Discussionmentioning
confidence: 95%
“…The younger age at presentation is a feature of breast cancer patients in most of the developing countries like India (Dinshaw et al, 2005;Saxena et al, 2005;Agarwal et al, 2007), SriLanka (Lokuhetty et al, 2009) and Cameroon (Ngowa et al, 2011). The younger age range of patients in Pakistan and the other developing countries may be explained by the younger age structure and the lower life expectancy of their women.…”
Section: 693 Clinicopathologic Profile Of Breast Cancer Patients In mentioning
confidence: 99%